ANALISIS DAN PROYEKSI KEBUTUHAN ENERGI SEKTOR TRANSPORTASI DI INDONESIA - Ari Kabul Paminto (Jurnal Energi dan Lingkungan (Enerlink), 2020)
Transportation is an important means for modern society to facilitate the mobility of people and goods.The transport sector consumes about 30% of the total national final energy consumption. In 2016,energy consumption in the transportation sector reached 331.7 million BOE (equivalent barrels of oil)with a fuel mix of 55.3% gasoline; 14.0% of diesel oil; 22.3% biosolar; 0.04% fuel oil, 0.07% natural gas;0.005% avgas, 8.15% aviation fuel and 0.04% electricity. The increasing demand for energy in thetransportation sector in Indonesia is largely due to the improvement and addition of transportinfrastructure in some parts of Indonesia, especially airports and the growth of low-cost airlines. In2050 it is projected that the use of gasoline and diesel oil will continue to increase with growth of 4.0%and 4.5% per year. Along with this, the growth of biodiesel continues to increase to 7.9% per year.While avtur utilization is projected to continue to grow with a growth rate of 6.8% per year.